Plastic behavior and fracture cross section of coiled tubing in the ram shearing process of subsea blowout preventer. (15th June 2022) - Li, Tao; Jiang, Dapeng; Liu, Bing; Zhao, Yongjie; Xie, Peng
Abstract: For studying the plastic behavior and fracture cross section of sheared drill pipe are of important aspects for evaluating the rams' shear performance of subsea blowout preventer, the plastic deformation and fracture cross section of drill pipe are analyzed based on the plastic deformation theory and the hypothesis that the deformation process of drill pipe is a four-plastic hinge or an eight-plastic hinge mechanism, respectively, according to different ram structure configuration. The elastic-plastic deformation process of CT90 tube in the simulated shearing process is obtained, the final fracture cross section of CT90 tube is approximately a rhombus circle, which is agreeing with the analytical and experimental results. Furthermore, the structure parameters research shows that ram or pipe structures have limited effect on the peak/terminal value of pipe stress. The major length of rhombus circle increases first and then decreases with the increase of ram's blade mouth thickness, decreases with the increase of ram's V-shape angle and pipe wall thickness, while the minor length shows an opposite trend. The larger pipe outer diameter is, the greater major/minor length of rhombus circle is and the growth rate of major length is significantly faster than that of minor length. Highlights: The fracture cross section of pipes is analyzed based on the plastic deformation theory of four or eight-plastic hinge mechanism. The plastic stress and fracture cross section of coiled tubing in the numerical shearing CT90 tube process was obtained. The analytical rhombus circle cross section of CT90 pipe is agreement with the numerical and experimental results. The sensitive parameters of the plastic stress and fracture cross section of coiled tubing were discussed in the shearing process.